Entrepreneurial Self-Efficacy In Entrepreneurial Intention: The Mediating Role Of Entrepreneurial Education - Luqman Amin; Annisa Fajri (UNIVED Press, 2024)
Unemployment, poverty and social inequality are big challenges for Indonesia in entering the free market and global competition.Today, individuals with a college degree experience stiff competition and difficulty in finding employment. Limited employment opportunities which have resulted in high unemployment rates have increased awareness of the importance of entrepreneurship. However, students' interest in entrepreneurship is still relatively low, causing them to hesitate to start a business because they are risk averse. Entrepreneurial intention, as the main predictor of entrepreneurial behavior, is important in understanding the entrepreneurial process. Factors influencing entrepreneurial intentions, especially entrepreneurial self-efficacy, have been widely researched.Apart from that, the role of the entrepreneurial ecosystem in forming entrepreneurial intentions has also received attention.This research investigates the influence of the entrepreneurial ecosystem, entrepreneurial education, and individual factors such as entrepreneurial self-efficacy on entrepreneurial intentions among business students. The findings show that the entrepreneurial ecosystem has a positive effect on entrepreneurial intentions, in line with previous research in the Western context. In addition, entrepreneurial education and individual factors such as entrepreneurial self-efficacy mediate this relationship. Practical implications include the need for universities to support students in developing an entrepreneurial mindset and improve entrepreneurship education to foster creativity. Limitations, such as the focus on business students and the cross-sectional design, offer avenues for future research to explore broader populations and use longitudinal designs.